PENGARUH VARIASI DIMENSI CATALYTIC CONVERTER BERBAHAN TEMBAGA NIKEL TERHADAP REDUKSI EMISI GAS BUANG SEPEDA MOTOR HONDA ASTREA - Ata Syifa' Nugraha; Ahmad Mahbub Zunaidi; Sudirman Rizki Ariyanto; Wahyu Robby Cahyadi (Journal of Automotive Vocational Education (JAVED), 2024)
This study was conducted to determine the effect of adding a copper nickel catalytic converter on CO and HC exhaust emissions on a Honda Astrea motorcycle. The scope of this study includes an analysis of the effect of variations in the dimensions of a copper nickel catalytic converter to reduce CO and HC exhaust emissions. This study uses an experimental method to compare the levels of CO and HC emissions in standard exhausts without catalysts with exhausts using catalysts from two experiments with different dimensions. Data were taken at several engine speeds (1000 rpm to 6000 rpm) using a Gas analyzer. The results showed that the catalytic converter of experiment 2 was able to reduce exhaust emissions significantly. The results of experiment 2, with a catalyst length of 10cm, were able to reduce CO emissions by an average of 37% and HC by 47%. The highest reduction in CO occurred at 6000 RPM (85%), while the largest reduction in HC occurred at 1000 RPM (81%). The conclusion of this study is that the copper-nickel catalytic converter from experiment 2 is more effective in reducing CO and HC exhaust emissions compared to the catalyst from experiment 1 or standard exhaust without a catalyst.